2000
DOI: 10.1046/j.1472-765x.2000.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated solar disinfection of water on infectivity of Salmonella typhimurium

Abstract: To determine whether cells of Salmonella typhimurium rendered nonculturable by simulated solar disinfection retain infectivity for mice. Bacteria suspended in water were exposed to UVA irradiation for up to 8 h. Culturability, determined by colony forming unit and Most Probable Number counts, fell by six log10 units, while cellular activity determined by the Kogure cell elongation test was retained by approximately 5% of the cells present after 8 h. Intraperitoneal doses of nonculturable cells and active but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 20 publications
6
39
0
2
Order By: Relevance
“…Some authors reported the existence of viable but non-culturable (VBNC) bacteria in environmental samples (Kjelleberg et al, 1993;Knight et al, 1990;Pommepuy et al, 1996 andRoszak andColwell, 1987), which would not be enriched in a pre-cultivation step and thus may escape detection. Medema et al (1992), Caro et al (1999) and Smith et al (2000) reported a loss of pathogenicity associated with non-culturability of S. typhimurium when subjected to seawater stress, solar and ultraviolet-C irradiation. Although the cultivation step excludes the detection of VBNC Salmonella, such bacteria most probably pose no significant threat to humans because of the minimum infectious dose of Salmonella (10 5 / 10 9 for S. typhi/ S. typhimurium respectively) required to initiate a disease (Le Minor, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported the existence of viable but non-culturable (VBNC) bacteria in environmental samples (Kjelleberg et al, 1993;Knight et al, 1990;Pommepuy et al, 1996 andRoszak andColwell, 1987), which would not be enriched in a pre-cultivation step and thus may escape detection. Medema et al (1992), Caro et al (1999) and Smith et al (2000) reported a loss of pathogenicity associated with non-culturability of S. typhimurium when subjected to seawater stress, solar and ultraviolet-C irradiation. Although the cultivation step excludes the detection of VBNC Salmonella, such bacteria most probably pose no significant threat to humans because of the minimum infectious dose of Salmonella (10 5 / 10 9 for S. typhi/ S. typhimurium respectively) required to initiate a disease (Le Minor, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Solar disinfection (SODIS) involves storing contaminated drinking water in transparent containers that are placed in direct sunlight for periods of up to 8 h before consumption (3,16). This technique is highly effective against a broad range of pathogens (4,8,9,15,17). Previous studies report reductions in the incidence of diarrhea in children who used SODIS compared with children who did not (3, 4).…”
mentioning
confidence: 99%
“…This technique is highly effective against a broad range of pathogens (4,8,9,15,17). Previous studies report reductions in the incidence of diarrhea in children who used SODIS compared with children who did not (3,4).…”
mentioning
confidence: 99%
“…However, 16 h of natural sunlight required for 1.3 log reduction of Bacillus subtilis endospores [10,15,28,39,[47][48][49][50].…”
Section: Inactivation Of Microorganismsmentioning
confidence: 99%